2016
DOI: 10.4196/kjpp.2016.20.3.287
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary stand-up physical activity enhances endurance exercise capacity in rats

Abstract: Involuntary physical activity induced by the avoidance of electrical shock leads to improved endurance exercise capacity in animals. However, it remains unknown whether voluntary stand-up physical activity (SPA) without forced simulating factors improves endurance exercise capacity in animals. We examined the eff ects of SPA on body weight, cardiac function, and endurance exercise capacity for 12 weeks. Twelve male Sprague-Dawley rats (aged 8 weeks, n=6 per group) were randomly assigned to a control group (CON… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Maximal endurance capacity can be enhanced with physical exercise, and different models in animals have been employed to prove this, including treadmill running, climbing, and swimming force, as well as others. Seo et al [ 18 ] utilized a voluntary stand-up physical activity (SPA) model, inducing rats to lift a load equivalent to their bodyweight, while the height of the food employed in cages increased gradually for 12 weeks. After the protocol, these authors reported a reduction of bodyweight but no significant changes in evaluation of skeletal muscle mass, heart weight, food consumption, and echocardiography that compared these with the control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maximal endurance capacity can be enhanced with physical exercise, and different models in animals have been employed to prove this, including treadmill running, climbing, and swimming force, as well as others. Seo et al [ 18 ] utilized a voluntary stand-up physical activity (SPA) model, inducing rats to lift a load equivalent to their bodyweight, while the height of the food employed in cages increased gradually for 12 weeks. After the protocol, these authors reported a reduction of bodyweight but no significant changes in evaluation of skeletal muscle mass, heart weight, food consumption, and echocardiography that compared these with the control.…”
Section: Discussionmentioning
confidence: 99%
“…Maximal endurance capacity (MEC) was determined during week one of the training protocol and during the last week of the protocol. The test consisted of incremental treadmill running, was started with 16.66 m/min, and the speed was gradually increased at 1.67 m/min every 30 s at 0 dof inclination until exhaustion [ 18 ]. The MEC was evaluated in terms of running distance and time.…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA from the hypothalamus was extracted with TRIzol (Invitrogen, Cergy Pontoise, France), and single-stranded cDNA was synthesized from 10 µg of total RNA using random hexamer primers (Applied Biosystems, Courtaboeuf, France). Real-time RT-PCR was performed to measure GLP-1 receptor levels, as previously described [ 29 ]. The following primers were used: GLP-1R forward primer 5’-GAA GAG TCC AAG CAA GGA GA-3’, reverse primer 5’-GAC CAA GGC AGA GAA AGA AA-3’, GAPDH forward primer 5’-CAG GAG CGA GAT CCC GC-3’, reverse primer 5’-CCT TTT GGC CCC ACC CT-3’.…”
Section: Methodsmentioning
confidence: 99%
“… 17 Mitochondrial biogenesis plays a role in transcriptional regulation by mediating regulatory factors such as peroxisome proliferator-activated receptor-g coactivator 1α, and downstream transcription factors such as nuclear respiratory factors 1 and 2 and mitochondrial transcription factor A. 18 , 19 Enhancement of mitochondrial biogenesis can be achieved not only through pharmacological intervention, 20 but also through exercise; therefore, exercise may inhibit mitochondrial dysfunction and thereby ameliorate age-related complications. In 1967, John Holloszy 21 first reported that exercise training improves mitochondrial biogenesis in aging skeletal muscle.…”
Section: Age-related Changes In the Mitochondria In Skeletal Musclementioning
confidence: 99%